Does Emotional Intelligence and Religiosity Affect the Ethical Judgment of Accounting Students? - Sulastri Sulastri; Ika Uswatun Kasanah (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2021)
This study aims to determine the effect of Emotional Intelligence and religiosity on the ethical judgment of accounting students. The sample in this study amounted to 210 accounting student respondents. The sample in this study was taken by the purposive sampling technique. The data in this study were collected using a questionnaire and then analyzed using descriptive statistical analysis and multiple linear regression. Based on the research results, it is known that Emotional Intelligence and religiosity have a significant positive effect on the ethical judgment in accounting students. This means that the higher the level of Emotional Intelligence and the level of religiosity of students, the more assertive they will be in making an ethical judgment. Thus, based on the results of this study, it is hoped that educational institutions, especially at the university level, will provide services and training to accounting students to improve their Emotional Intelligence and religiosity. Also, companies can add indicators of Emotional Intelligence and religiosity in recruiting accounting staff and corporate auditors, to increase the company's credibility and integrity in the future.